(untitled) (Advancements in Homeopathic Research, 2022)
Objective: Theaimof this pilot study was to ascertain the effect of Amalaki as an add on therapy to conventional treatment in improving the Quality of Life of patients of type 2 diabetes mellitus using WHOQOL - BREF Scale. Materials &Methods: Thissingle-blind randomised placebo controlled trialwas conducted in Dr. Madan Pratap Khunteta Homoeopathic Medical College, Hospital & Research Centre, Jaipur, Rajasthan, from May 2017 to June 2018. A total of 40 participants between age group of 20-60 years, were randomlyallocated to two groups of 20 participants in each group to receive either Amalaki 30 CH or placebo thrice daily for 90 days. Assessment was done at baseline and at end of treatment using ‘WHOQOL BREF Scale. Observations and Results: 4 participants were dropped and 36 participants completed the study, with 18 participants in each Group A and Group B and were analyzed after anintervention period of 90 days. The results were drawn over four domains of Quality of Life i.e.physical health, psychological, social relationships & environment, and the mean difference was compared. Conclusion: Overall, the result of the present study show that the physical domain, psychological domain, social relationship domain and environmental domain of quality of life were significantly improved after taking Amalaki 30 CH as an add on therapy to conventional treatment in Diabetes mellitus type 2.